2021
DOI: 10.3390/cells10112984
|View full text |Cite
|
Sign up to set email alerts
|

Rho GTPases in Skeletal Muscle Development and Homeostasis

Abstract: Rho guanosine triphosphate hydrolases (GTPases) are molecular switches that cycle between an inactive guanosine diphosphate (GDP)-bound and an active guanosine triphosphate (GTP)-bound state during signal transduction. As such, they regulate a wide range of both cellular and physiological processes. In this review, we will summarize recent work on the role of Rho GTPase-regulated pathways in skeletal muscle development, regeneration, tissue mass homeostatic balance, and metabolism. In addition, we will present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 137 publications
(221 reference statements)
0
9
0
Order By: Relevance
“…In addition, RHO-GTPase genes were higher in both fractions with overload relative to sham (Figure 2A and 2B). RHO-GTPases are implicated in muscle mass regulation, but their role in load-induced hypertrophy is still being defined (47). Genes related to epigenetic control of gene expression (specifically histones and Dnmt1) were enriched in the non-EU fraction with overload (Figures 2D and 2E).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…In addition, RHO-GTPase genes were higher in both fractions with overload relative to sham (Figure 2A and 2B). RHO-GTPases are implicated in muscle mass regulation, but their role in load-induced hypertrophy is still being defined (47). Genes related to epigenetic control of gene expression (specifically histones and Dnmt1) were enriched in the non-EU fraction with overload (Figures 2D and 2E).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Consistently, we found that DP2 activation markedly increased RhoA/ROCK2 activity, the inhibition of which markedly promoted NFATc1‐guided oxidative muscle fibre transformation. Indeed, RhoA/ROCK signalling can impede muscle development at the embryonic stage, and the blockage of ROCK enhances the beneficial effects of corticosteroid treatment in dystrophic mice 37 . PKA activation suppresses RhoA/ROCK signalling in various cell types, including muscle cells, such as cardiomyocytes and smooth muscle cells 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, RhoA/ROCK signalling can impede muscle development at the embryonic stage, and the blockage of ROCK enhances the beneficial effects of corticosteroid treatment in dystrophic mice. 37 PKA activation suppresses RhoA/ROCK signalling in various cell types, including muscle cells, such as cardiomyocytes and smooth muscle cells. 38 , 39 Similarly, we found that Gi‐coupled DP2 inhibited PKA activity to enhance RhoA signalling and suppress NFATc1‐mediated oxidative muscle fibre transition.…”
Section: Discussionmentioning
confidence: 99%
“…As a Rho GTPase, Cdc42 plays a key role in a variety of cellular processes, and activated Cdc42 can mediate signaling cascades and activate various downstream effectors, thereby leading to many cellular activities, such as cell adhesion, motility, polarity, cytokinesis, and growth [ 26 , 27 , 28 ]. In the late stage of skeletal muscle differentiation, the expression of active Cdc42 increases, which plays an important role in myogenic differentiation [ 29 ]. The effect of Cdc42 on myogenesis has been demonstrated in mouse, human, and avian cells [ 15 , 17 , 30 , 31 ], but whether it is positive or negative remains controversial.…”
Section: Discussionmentioning
confidence: 99%